Chemical composition, quality attributes and antioxidant activity of stirred-type yogurt enriched with Melastoma dodecandrum Lour fruit powder. Issue 3 (24th January 2022) - Rashwan, Ahmed K.; Karim, Naymul; Xu, Yang; Cui, Haoxin; Fang, Jie; Cheng, Kejun; Mo, Jianling; Chen, Wei
Abstract : Incorporation of  Melastoma dodecandrum  Lour fruit powder as a promising functional ingredient for stirred-type yogurt (STY) improved physicochemical properties, polyphenol contents, antioxidant activity, microstructure, and texture of STY. Abstract : This study for the first time used Melastoma dodecandrum Lour fruit powder (MDLP) as a novel functional ingredient for improving the quality of stirred-type yogurt (STY). Physicochemical properties, polyphenol content, antioxidant activity, textural analysis, fat globules, microstructure, and sensorial properties of MDLP-fortified STY were evaluated during storage (at 4 °C). The results indicated that MDLP significantly ( p < 0.05) improved the total phenolics, flavonoids, anthocyanins, and proanthocyanidins, as well as increased the antioxidant activity of fortified yogurts compared to an STY-control. Interstitially, MDLP altered the structure of STY, making it firmer and more cohesive, increased its viscosity index, and significantly reduced whey and fat globule release compared to the STY-control during cold storage. Among all MDLP concentrations, 1% MDLP-fortified STY showed the best results followed by 0.5%. This study concluded that MDLP can be used as a potential nutritious ingredient and as a natural stabilizer for yogurt and related products.